Political Yardstick Competition, Economic Integration, and Constitutional Choice in a Federation - Martin Bodenstein; Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper investigates the behavior of rent-seeking politicians in an environment of increasing economic integration. The focus of the paper is on the implications of globalization-induced political yardstick competition for constitutional design with a view to the current discussion in the European Union. In contrast to the established literature, we carefully portray the double-tiered government structure in federal systems. The number of lower-tier governments and the allocation of policy responsibilities to the two levels of government are subject to constitutional choice.
Keywords: 330; Economic Integration; Federalism; Political Economy; Yardstick Competition